The impact of personal medical savings accounts on healthcare utilization and out-of-pocket costs in public basic health insurance: a national cross-sectional study - Yang, Jinming; Tao, Wenjuan; Qu, Xing (Frontiers in Public Health, 2025)
ObjectivesPrevious research has shown that the implementation of personal medical savings accounts in health insurance can impact health utilization and medical cost through enhancing individual responsibility for their own health. The aim of this study was to investigate whether there are differences in various healthcare utilization and out-of-pocket payment ratios between insured individuals with and without personal medical savings accounts in the context of basic medical insurance in China.MethodsA nationally representative cross-sectional data from the China Health and Retirement Longitudinal Study was used to analyze. Seemingly Unrelated Regression analysis was conducted to examine the potential impact of personal medical savings accounts on the utilization rates and self-payment ratios for outpatient services, hospitalization, dental treatment, and physical examinations. Heckman selection model was used as a sensitivity analysis to test the robust of original results.ResultsA total of 15,628 individuals were included in the analysis. Among them, 95.5% were covered by basic medical insurance, while only 12.8% had a personal medical savings account. Possessing a personal medical savings account was significantly associated with increased utilization of dental services (OR: 1.327, 95% CI: 1.05–1.67) and a higher frequency of physical examinations (OR: 2.271, 95% CI: 1.86–2.77). This effect was not significant in outpatient and inpatient health service utilization. Furthermore, having a personal medical savings account was significantly associated with lower out-of-pocket payment ratios across various healthcare services. Specifically, individuals with such accounts experienced a 15.8 percentage point reduction in outpatient services, a 22.1 percentage point reduction in inpatient services, and a 13.4 percentage point reduction in dental services.ConclusionThe study revealed disparities between individuals with and without personal medical savings accounts in China. While these accounts can cover the insurer’s regular medical expenses, their effect on high-cost expenses appears to be limited. These findings suggest that reforms in medical insurance should focus on reducing the gap between insured individuals with and without personal medical savings accounts.